2000
DOI: 10.1007/s004649900014
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted abdominoperineal resection for low rectal adenocarcinoma

Abstract: Laparoscopic-assisted abdominoperineal resection allowed earlier postoperative recovery, with equal oncological clearance, morbidity, mortality, disease-free interval, and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 18 publications
(15 reference statements)
2
34
1
10
Order By: Relevance
“…In order to avoid repositioning of the robotic cart during surgery, we mobilised the sigmoid-descending colon with conventional laparoscopic techniques first, before we brought in the robotic cart for telerobotic-assisted rectal mobilisation. With this hybrid technique, our case can be finished within 240 min, which compares favourably with the mean operative time of 215 min in our previous report on laparoscopic-assisted abdominoperineal resection for low rectal cancer [19] . Table 2 summarises the published studies comparing telerobotic-assisted colorectal surgery using the da Vinci surgical system versus conventional laparoscopic colorectal surgery [20][21][22][23] .…”
Section: Discussionsupporting
confidence: 76%
“…In order to avoid repositioning of the robotic cart during surgery, we mobilised the sigmoid-descending colon with conventional laparoscopic techniques first, before we brought in the robotic cart for telerobotic-assisted rectal mobilisation. With this hybrid technique, our case can be finished within 240 min, which compares favourably with the mean operative time of 215 min in our previous report on laparoscopic-assisted abdominoperineal resection for low rectal cancer [19] . Table 2 summarises the published studies comparing telerobotic-assisted colorectal surgery using the da Vinci surgical system versus conventional laparoscopic colorectal surgery [20][21][22][23] .…”
Section: Discussionsupporting
confidence: 76%
“…Because it was not possible to separate data between the two groups, we decided to extend the analysis to both treatments and redesigned the study protocol accordingly, after verifying that the procedure was equally represented, with no selection bias in both groups in each of the studies. This way, we also included two reports entirely focusing on abdominoperineal resections [29,36]. We conducted two separate analyses, one including and one excluding these reports, only to find that the results substantially overlapped, so we opted to include them into the analysis.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Previous reports showed that operative mortality is comparable between laparoscopic and open APR (19,23,24). These studies also reported that morbidity was significantly lower in patients who underwent laparoscopic APR compared to open approach (19,23,24).…”
Section: Discussionmentioning
confidence: 82%
“…It has been demonstrated that laparoscopic APR is associated with better and faster bowel function recovery, less blood loss, shorter hospitalization and better rectal cancer prognosis and outcome (13)(14)(15). Several meta-analyses compared the laparoscopic and open APR regarding short-and long-term outcomes (16)(17)(18)(19). They demonstrated that laparoscopic APR is associated with earlier postoperative recovery (20,21) and less postoperative morbidity (22).…”
Section: Introductionmentioning
confidence: 99%